A wide output range voltage-mode buck converter with fast voltage–Tracking speed for RF power amplifiers. Issue 1 (January 2015) - Xu, Shen; Sun, Fengfeng; Yang, Miao; Han, Caixia; Sun, Weifeng; Lu, Shengli
Abstract A high switching frequency voltage-mode buck converter with fast voltage-tracking speed, wide output range and PWM/PSM control strategy for radio frequency (RF) power amplifiers (PAs) has been proposed. To achieve the fast voltage-tracking speed, the maximum charging and discharging current control method has been used, and the filter inductor and capacitor values are reduced. A novel compensated error amplifier (EA) is presented to realize the wide output range. The investigated converter has been fabricated with GF 0.35 μm CMOS process and can operate at 5 MHz with the output voltage range from 0.6 V to 3.4 V. The experimental results show that the voltage-tracking speed can achieve 8.8 μs/V for up-tracking and 6 μs/V for down-tracking. Besides, the recovery time is less than 8 μs when the load change step is 400 mA.